Synthesis and Characterization of Polyaniline / [BMIM][BF4] Polyionic Liquid by Interfacial Polymerization - Mahmood, Reem Y.; Kareem, Aseel A.; Polu, Anji Reddy (Iraqi Journal of Science, 2024)
Polyaniline (PANI) was prepared by polymerization via the chemical oxidation of aniline monomer with ammonium persulfate as the initiator. The interfacial polymerization method was used to prepare PANI/1-butyl-3-methylimidazolium tetrafluoroborate [BMIM][BF4] polyionic liquid (PIL). The obtained PANI/ [BMIM][BF4] PIL was investigated by the XRD, EDX, SEM, FTIR, and UV-Visible characterizations. X-ray diffractogram of PANI showed five prominent characteristic peaks at 27.1°, 24o, 21.8°, 19.8°, and 18.2°. This demonstrates the semi-crystalline character of the polyaniline produced through the interfacial polymerization process. Incorporation of [BMIM][BF4] into PANI reduced the crystalline phase and enhanced amorphicity. From the EDX pattern, several elements appeared in this test; oxygen had of the highest weight percentage of 54.2%. The SEM image showed a clear hierarchal porous structure with nano-sticks particles and forms a cross-linked framework between PANI and [BMIM][BF4]. From FTIR spectra of PIL, a prominent absorption peak at 3163.26 cm-1 was noted because of the N-H stretching vibrations present in the polymer. The UV-Vis spectra for PANI/[BMIM][BF4] polyionic liquid showed three peaks between 200 and 1060 nm. These bands result from π → π* and n → π* transitions, which are related to the excitement absorption of benzenoid and quinoid groups.